Diagnosis of Chronic Obstructive Pulmonary Disease and Regulatory Mechanism of miR-149-3p on Alveolar Inflammatory Factors and Expression of Surfactant Proteins A (SP-A) and D (SP-D) on Lung Surface Mediated by Wnt Pathway - Zhang, Xiuli; Wang, Yaping; He, Xiang; Sun, Zerui; Shi, Xuefeng (Computational intelligence and neuroscience, 2022)
Objective. To study the mechanism of chronic obstructive pulmonary disease (COPD) in diagnosing alveolar factors and analyze the effect of miR-149-3p on alveolar inflammatory factors and the expression of surfactant protein D (SP-D) and SP-A on the lung surface mediated by Wnt pathway. Methods. Patients with stable COPD were taken as the research subjects, and healthy volunteers as the control group. Cardiac color Doppler ultrasound was adopted to measure the ventricular structure of patients. The ultrasound simulation method was introduced in the ultrasound imaging. The ultrasound image was processed based on the intelligent ultrasound simulation algorithm. The changes in the structure of the left and right ventricles were analyzed and compared in the two groups. The expression changes of miR-149-3p, Wnt1, β-catenin, RhoA, and Wnt5a in lung tissues of mice in three groups were detected, as well as the content of tumor necrosis factor- (TNF-) α, IL-1β, interleukin (IL-6), nuclear factor kB (NF-kB), and other inflammatory factors in bronchoalveolar tissues of mice in three groups. Results. The position where the attenuation ratio was less than 0.92 in the experiment under the ultrasonic simulation algorithm had a gray value of 50. Compared with the control group, the right ventricular mass index of patients with stable COPD was statistically considerable (P<0.05). In patients with stable COPD, the overall right ventricular longitudinal strain, right ventricular diastolic longitudinal strain rate (RV DLSR), right ventricular diastolic circumferential strain rate, and right ventricular longitudinal displacement were significantly impaired (P<0.05). The content of miR-149-3p in the lung tissue of the model group was dramatically inferior to that of the control group and the interference group (P<0.05). The contents of Wnt1, β-catenin, RhoA, and Wnt5a in the lung tissue of the model group were dramatically superior to those of the control group (P<0.05). In addition, the expressions of TNF-α, IL-1β, IL-6, and NF-kB in the alveolar lavage fluid of the model group were statistically different from those of control group (P<0.05). The expression levels of SP-D and surfactant protein A (SP-A) in the COPD group were also statistically different from those of control group (P<0.05). Conclusion. miR-149-3p regulated the expression of Wnt1, β-catenin, RhoA, and Wnt5a, which also affected the signal transmission of the Wnt pathway, causing changes in the expression of alveolar inflammatory factors. Eventually, it affected the development of COPD.